The Benefits of the Video Abstract as a Newly Emerging Academic Genre (English version) - Lucas Accastello; Luisina Quinteros (Ñawi: Arte, Diseño y Comunicación)
After detailed research done on the existing literature, the present article aims at conceptualizing the genre video abstract by focusing on its defining characteristics and the benefits it may bring to both researchers and also the non-academic community. This newly emerging type of scientific summary presents some technical, material and social characteristics which will be developed in this paper. As multimodal artifacts, video abstracts provide authors with the opportunity to make use of an array of semiotic resources in order to convey meaning and communicate research findings. Having insurmountable semiotic potential, this genre offers several advantages, but one of the most relevant ones for the scientific community is the possibility of using the video abstract to propel the dissemination of science and knowledge to a wider audience.